Relationship Between Simple Oxygen Extraction Ratio to Cardiac Index and Mean Arterial Pressure in Septic Shock Patient Treated in ICU Dr. Sardjito Hospital Yogyakarta - irianto, helen yudi; Jufan, Akhmad Yun; Widodo, Untung (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2023)
Background : Oxygen extraction ratio (O2ER)  having any relationship with  cardiac index and mean arterial pressure in septic shock patient.Objective: Discover any relation between simplified oxygen extraction ratio with cardiac index and mean arterial pressure in shock septic condition at ICU of RSUP Dr Sardjito YogyakartaMethod : 32 subject with crossectional study was performed by inclution criteria such as : patient in ICU diagnosed as shock septic, more than 18 years old, inerted cvc in right atrium, inserted arterial line in  arterial radialis or brachialis which connected mostcare. BGA (arterial and venous ) sampel was taken by I-STAT® together with recording mean arterial pressure (MAP) and cardiac index value.Result :  Correlation between O2ER and cardiac index p=0,009 (p<0,05) with r -0,456. Correlation between O2ER and MAP p=0,006 (p<0,05) with r-0,474.Conclusion :Anesthesia management of TGA TGA cases is to avoid reducing cardiac output and SVR and keep the PVR lower than the SVR.